Geomagnetic paleosecular variation recorded in Plio-Pleistocene volcanic rocks from Possession Island (Crozet Archipelago, southern Indian Ocean) (Dataset) ... - Camps, Pierre; Henry, Bernard; Prévot, Michel; Faynot, Liliane (Magnetics Information Consortium (MagIC), 2011)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Geomagnetic paleosecular variation recorded in Plio-Pleistocene volcanic rocks from Possession Island (Crozet Archipelago, southern Indian Ocean) ...